A retrospective analysis of maternal mortality in an urban tertiary care hospital - Bhushan, Nishu; Manhas, Aakriti; Dogra, Anju (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The aims of the study were to generate information regarding causes and complications leading to maternal deaths in an urban tertiary care centre and to find if any of the causes are preventable. Methods: The medical records of all maternal deaths occurring over a period of 4 years between January 2015 and December 2018 were reviewed. Results: Maternal mortality ratio ranged between 127 and 48 per 1, 00,000 births in the study. The causes of deaths were haemorrhage (29.47%), pregnancy-induced hypertension (PIH) (28.42%), anaemia (12.63%), sepsis (9.47%), thromboembolism (6.31%), hepatic causes (5.26%), blood reactions (3.15%), heart diseases (2.10%), central nervous system (CNS) related (1.05%) and others (2.10%). Maximum deaths occurred in women between 21-30 years of age. Mortality was highest in post-natal mothers (70.52%). Conclusions: Overall maternal mortality due to direct obstetric causes was (73.68%), indirect obstetric causes (22.10%) and unrelated causes (4.2%).